Lecture at the Third All-Russian Youth School-Seminar with International Participation “Innovative Aspects of Basic Research on Urgent Problems of Physics”, October 25-30, 2009; Bulletin of the Lebedev Physics Institute; Vol. 37, № 1 - Mesyats G. A. Gennady Andreyevich (2010, 2010)
В фонде НТБ ТПУ отсутствует